Absolute stress measurement of structural steel members with ultrasonic shear-wave spectral analysis method. (January 2019) - Li, Zuohua; He, Jingbo; Teng, Jun; Huang, Qin; Wang, Ying
Absolute stress in structural steel members is an important parameter for the design, construction, and servicing of steel structures. However, it is difficult to measure via traditional approaches to structural health monitoring. The ultrasonic time-of-flight method has been widely studied for monitoring absolute stress by measuring the change in ultrasonic propagation time induced by stress. The time-of-flight of the two separated shear-wave modes induced by birefringence, which is particular to shear waves, is also affected by stress to different degrees. Their synthesis signal amplitude spectrum exhibits a minimum that varies with stress, which makes it a potential approach to evaluating uniaxial stress using the shear-wave amplitude spectrum. In this study, the effect of steel-member stress on the shear-wave amplitude spectrum from the interference of two shear waves produced by birefringence is investigated, and a method of uniaxial absolute stress measurement using shear-wave spectral analysis is proposed. Specifically, a theoretical expression is derived for the shear-wave pulse-echo amplitude spectrum, leading to a formula for evaluating uniaxial absolute stress. Three steel-member specimens are employed to investigate the influence of uniaxial stress on the shear-wave pulse-echo amplitude spectrum. The testing results indicate that the amplitude spectrum changes with stress and that the inverse of the first characteristic frequency in the amplitude spectrum and its corresponding stress exhibit a near-perfect linear relationship. On this basis, the uniaxial absolute stress of steel members loaded by a test machine is measured by the proposed method. Parametric studies are further performed on three groups of steel members made of 65# steel and Q235 steel to investigate the factors that influence the testing results. The results show that the proposed method can measure and monitor steel-members uniaxial absolute stress on the laboratory scale and has potential to be used in practical engineering with specific calibration.